Comprehending Metal Particle Combustion: a Path Forward. Issue 7 (19th May 2022) - Altman, Igor; Pantoya, Michelle
Abstract: The paper discusses the physics required for accurate modeling of metal particle combustion and includes aspects previously neglected. Specifically, three physical phenomena are emphasized: 1) internal boiling on the condensed oxide‐metal interface; 2) condense‐luminescent loss during nano‐oxide formation; and, 3) suppressed heat transfer on the metal particle surface due to a low energy accommodation coefficient (EAC) are essential. The last two phenomena were explored in previous work. Internal particle interface boiling detailed in the current work enables the semi‐heterogeneous combustion of Al particles, an important process needing attention for accurate modeling. The interface boiling mechanism allowing for the semi‐heterogeneous combustion explains a number of experimental puzzles related to metal particle combustion. In particular, the semi‐heterogeneous combustion justifies the coexistence of two burning regimes of Al particles (slow and fast) recently observed. Based on reported findings, revising current numerical models for metal particle combustion to include these three physical phenomena is necessary. Implications toward enhancement of energetic performance for metal‐containing formulations are also discussed. Abstract :